HBIM approach to implement the historical and constructive knowledge. The case of the Real Colegiata of San Isidoro (León, Spain) - Santoni, Arianna; Martín-Talaverano, Rafael; Quattrini, Ramona; Murillo-Fragero, José Ignacio (Virtual archaeology review, 2021)
The development of Historic Building Information Modelling (HBIM) focuses (among other uses) on the adaptation of the BIM methodology to the historical building’s features, as well as on increasing geometric accuracy and on model data enrichment. Regarding the first issue, it can be underlined, on the one hand, that historical buildings are the result of a sequence of transformations that take place throughout their whole history; they cannot be considered as unitary objects that have been created in a single moment. Therefore, they have a temporal sequence which can be understood as the essence of their evolving nature. On the other hand, historical architecture has different construction materials and techniques, with other kinds of features and pathological processes that are quite different from those of contemporary buildings. In this line, this study proposes a new workflow that allows outlining new criteria that include both the temporal sequence and the constructive features of historical buildings. For this purpose, the case study of the Real Colegiata of San Isidoro in León (Spain) has been considered. In order to create the model, several modelling strategies have been used to compare both the results and the time spent in this task. Then, the model has been divided into several parts, both in terms of constructive criteria and temporal stratification, and thus, the database and the implemented information have been organized following such essential aspects of the historical building. Finally, to provide an advanced and more efficient use of the information, customized queries have been created using Dynamo, allowing searching with combined criteria and the isolation and visualization of the resulting elements. This could be helpful for both research and conservation and management activities.Highlights:A comparison of modelling strategies applied to historical buildings taking into consideration their singularities and estimation of required times and benefits.The division and taxonomy of the model to incorporate both the temporal sequence and the constructive aspects, allowing enrichment of the HBIM model with customized parameters.The development of queries generated in Dynamo to allow customized and combined searches of data, optimizing the use of the database.